Issuing Government Bonds to Finance Bank Recapitalization and Restructuring : Design Factors that Affect Banks' Financial Performance - Andrews, Michael (Washington, D.C. : International Monetary Fund, 2003)
Bonds issued by the government or government agencies are often used to finance bank restructuring following a systemic crisis. Many conflicting considerations affect the design of the bonds used to pay for public sector investment in bank equity or the purchase of distressed assets from banks. Some bond features can leave restructured banks facing significant risks, laying the foundation for future banking sector problems. Sovereign default makes publicly financed bank restructuring more difficult, but it is still possible to carry out if banks receive sufficient interest income to provide a margin over their cost of funds.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet